2021
DOI: 10.1167/iovs.62.7.3
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo–Induced Bone Marrow-Derived Myeloid Suppressor Cells Prevent Corneal Allograft Rejection in Mice

Abstract: PURPOSE.To investigate the effects of ex vivo-induced bone marrow myeloid-derived suppressor cells (BM-MDSCs) on allogeneic immune responses in corneal transplantation. METHODS.Bone marrow cells from C57BL/6J (B6) mice were cultured with IL-6 and GM-CSF for four days. The ex vivo induction of the BM-MDSCs was assessed using flow cytometry, inducible nitric oxide synthase (iNOS) mRNA expression using reverse transcriptionquantitative polymerase chain reaction, and nitric oxide (NO) production in allogeneic stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
13
0
4
Order By: Relevance
“…For example, it has been reported that third-party allogeneic mesenchymal stromal cells could prevent rejection in a pre-sensitized high-risk model of corneal transplantation [134]. Moreover, our previous research has revealed the immunoregulatory effect of donor's bone-marrow-derived suppressor cells in a mouse model of high-risk corneal transplantation [76]. These cellular therapies may provide a potential method of dealing with neovascularization and graft rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been reported that third-party allogeneic mesenchymal stromal cells could prevent rejection in a pre-sensitized high-risk model of corneal transplantation [134]. Moreover, our previous research has revealed the immunoregulatory effect of donor's bone-marrow-derived suppressor cells in a mouse model of high-risk corneal transplantation [76]. These cellular therapies may provide a potential method of dealing with neovascularization and graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…DCs also play an important role in the innate detection of pathogens and activation of the adaptive immune system [75]. Immature DCs (with lower levels of HLA-DR, CD80, CD83, and CD86), including bone-marrow-derived immunosuppressive cells [76], could induce T-cell tolerance, whereas mature DCs induce T-cell immunity [77][78][79][80][81]. Immature DCs were found to be associated with longer allograft survival compared with normal controls during the immune response process of corneal transplantation (Figure 2A) [45].…”
Section: Discussionmentioning
confidence: 99%
“…Inflamed, neovascularized, “high-risk” recipient beds were created 7 , 8 , 45 by placing three intrastromal sutures into the central cornea 14 days before corneal transplantation. As described previously 7 9 , 46 , 47 , C57BL/6 corneas were grafted onto BALB/c host beds.…”
Section: Methodsmentioning
confidence: 99%
“…Graft neovascularization score, opacity score, and survival rate were evaluated using a slit lamp biomicroscope 7 , 45 , 47 . We used a standardized scoring system to calculate the neovascularization (range 0–8) and opacity (range 0–5+) scores.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, VEGFR-3 inhibition could be used as lymphatictargeted immunomodulatory therapy to prevent acute and chronic rejection in cardiac allografts [20]. Reduction of lymphangiogenesis has been reported to protect allogenic heart transplants and beyond [19,21]. Therefore, it is important to understand the diversity and complexity of the interplay between lymphangiogenesis and transplantation immunology.…”
Section: Introductionmentioning
confidence: 99%